How to do things with gifts: Gjafa-Refs þáttr and Auðunar þáttr vestfirzka - Barreiro, Santiago Francisco (2015)
The aim of this article is to assess the ideology of two short storiesfocused on gift-giving and composed in medieval Iceland: Gjafa-Refs þáttr and Auðunar þáttr vestfirzka. Our hypothesis is that the texts, while sharing a similar narrative motif, represent different ideological stances that can be associated with the transformations undertaken by Icelandic society during the thirteenth century. We argue that while the earlier Tale of Auðunn exemplifies a story of social promotion based almost purely on personal qualities, the later Tale of Gift-Refr adds supraindividual conditionsto explain the success of its main character, emphasizing good lineage and aristocratic patronage.